AraC-Type Regulator Rbf Controls the Staphylococcus epidermidis Biofilm Phenotype by Negatively Regulating the icaADBC Repressor SarR - Rowe, Sarah E. (J Bacteriol, 2016)
Regulation of icaADBC-encoded polysaccharide intercellular adhesin (PIA)/poly-N-acetylglucosasmine (PNAG) production in staphylococci plays an important role in biofilm-associated medical-device-related infections. Here, we report that the AraC-type transcriptional regulator Rbf activates icaADBC operon transcription and PIA production in Staphylococcus epidermidis. Purified recombinant Rbf did not bind to the ica operon promoter region in electrophoretic mobility shift assays (EMSAs), indicating that Rbf regulates ica transcription indirectly. To identify the putative transcription factor(s) involved in Rbf-mediated icaADBC regulation, the ability of recombinant Rbf to interact with the promoter sequences of known icaADBC regulators was investigated. Recombinant Rbf bound to the sarR promoter and not the sarX, sarA, sarZ, spx, and srrA promoters. Reverse transcription (RT)-PCR demonstrated that Rbf acts as a repressor of sarR transcription. PIA expression and biofilm production were restored to wild-type levels in an rbf sarR double mutant grown in brain heart infusion (BHI) medium supplemented with NaCl, which is known to activate the ica locus, but not in BHI medium alone. RT-PCR further demonstrated that although Rbf does not bind the sarX promoter, it nevertheless exerted a negative effect on sarX expression. Apparently, direct downregulation of the SarR repressor by Rbf has a dominant effect over indirect repression of the SarX activator by Rbf in the control of S. epidermidis PIA production and biofilm formation. IMPORTANCE The importance of Staphylococcus epidermidis as an opportunistic pathogen in hospital patients with implanted medical devices derives largely from its capacity to form biofilm. Expression of the icaADBC-encoded extracellular polysaccharide is the predominant biofilm mechanism in S. epidermidis clinical isolates and is tightly regulated. Here, we report that the transcriptional regulator Rbf promotes icaADBC expression by negatively regulating expression of sarR, which encodes an ica operon repressor. Furthermore, Rbf indirectly represses the ica operon activator, SarX. The data reveal complicated interplay between Rbf and two Sar family proteins in fine-tuning regulation of the biofilm phenotype and indicate that in the hierarchy of biofilm regulators, IcaR is dominant over the Rbf-SarR-SarX axis.